Osteoporosis genome‐wide association study variant c.3781 C>A is regulated by a novel anti‐osteogenic factor miR‐345‐5p. Issue 3 (12th January 2020) - Wang, Ya; Ye, Weiyuan; Liu, Yuyong; Mei, Bing; Liu, Xinhong; Huang, Qingyang
Abstract: Upstream transcription factor family member 3 ( USF3 ) c.3781C>A (rs1026364) in the 3′‐untranslated region (3′‐UTR) has been firmly associated with bone mineral density (BMD) in genome‐wide association study (GWAS). However, the molecular mechanism by which it influences BMD and osteoporosis is unknown. Bioinformatics analyses suggested that the risk c.3781A allele creates a target site for hsa‐miR‐345‐5p binding. Luciferase assay validated that the c.3781A allele displayed significantly lower luciferase activities than the c.3781C allele in the human osteoblast cell line hFOB1.19, osteosarcoma cell lines U‐2OS and Saos‐2, and embryonic kidney cell line 293T. Furthermore, hsa‐miR‐345‐5p regulated USF3 expression on both messenger RNA and protein levels in hFOB1.19 and U937 cells with heterozygous A/C genotype. Transfection of hsa‐miR‐345‐5p antagomiR in heterozygous hFOB1.19 cells significantly increased the expression of osteogenic marker genes RUNX2, OSTERIX, COL1A1, ALP, OPN, OCN, and alkaline phosphatase activity and matrix mineralization level. Importantly, we found that hsa‐miR‐345‐5p also inhibits osteoblast maturation in cell lines U‐2OS with hsa‐miR‐345‐5p nonbinding C/C genotype by targeting RUNX3 and SMAD1 . Our findings uncovered a novel pathogenetic mechanism of osteoporosis by GWAS variant c.3781C>A‐mediated disruption of hsa‐miR‐345‐5p binding at the 3′‐UTR of USF3 and the functional role of hsa‐miR‐345‐5p in osteogenic differentiation.